EDUCATIONAL ENVIRONMENT IN THE IMPLEMENTATION OF CHARACTER EDUCATION - Yudhie Suchyadi; Amalia Suryani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
the meaning and role of the environmenteducation in character education. The analytical method used indiscussion of the main topic using an effectual causal analysis model withexamines rational relationships, which analyzes the cause-and-effect relationships betweeneducational environment on character education with the main source ofliterature review. The results of the discussion show that the educational environmenthave a great influence on character education. This article concludesthat the implementation of character education needs to be supported by the environmentgood education